Investigating Interdiscursivity in Hospital Strategic Plans Using Foucauldian Discourse Analysis - Antoinette Fage-Butler (Hermes, 2015)
Critical genre analysis (CGA) investigates the impact of context on genres by analyzing interdiscursivity (the integration of discourses in genres), but there has been a shortage of discussion of specific methods. This paper demonstrates that Foucauldian discourse analysis (FDA) – specifically, statement function analysis – constitutes a very useful approach with which to analyze interdiscursivity in CGA. Analysis of the move of “priorities/goals” (Cornut et al. 2012)  in three strategic plans produced by British hospitals using FDA reveals three main discourses: strategic management, public service accountability, and patient centeredness. As interdiscursive analysis reveals the discursive foundations of organizational practices, CGA is well-positioned to make many valuable contributions to organizational research.